2021
DOI: 10.3389/fcell.2021.642108
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Accumulation Enhances von Willebrand Factor-Induced Platelet P-Selectin Translocation in a PI3K/Akt Pathway-Dependent Manner

Abstract: Platelet adhesion and activation through the interaction of von Willebrand factor (VWF) with platelet glycoprotein (GP) Ibα are the early key events in hemostasis and thrombosis especially under high blood shear stress. P-selectin translocation from α granule to the cell surface is a typical platelet function phenotype, which makes the platelet-induced inflammatory response of flowing leukocytes possible and can be induced by either chemical agonists (thrombin, ADP, etc.) or high blood shear stress, but regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Of note, their down-regulation indicated anti-inflammatory effects of uPB-Exo. Collected evidences have shown that the downregulated genes, including colony stimulating factor 3 [ 75 ], matrix metallopeptidase 9 [ 76 ], interleukin 1 alpha [ 77 ], interleukin 1 beta [ 78 ], interleukin 7 receptor [ 79 ] and Von Willebrand factor [ 80 ] could be regulated by PI3K/AKT pathway. Meanwhile, KEGG pathway enrichment analysis demonstrated that numerous down-regulated genes were significantly enriched PI3K-Akt pathway in FLS with uPB-Exo treatment ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, their down-regulation indicated anti-inflammatory effects of uPB-Exo. Collected evidences have shown that the downregulated genes, including colony stimulating factor 3 [ 75 ], matrix metallopeptidase 9 [ 76 ], interleukin 1 alpha [ 77 ], interleukin 1 beta [ 78 ], interleukin 7 receptor [ 79 ] and Von Willebrand factor [ 80 ] could be regulated by PI3K/AKT pathway. Meanwhile, KEGG pathway enrichment analysis demonstrated that numerous down-regulated genes were significantly enriched PI3K-Akt pathway in FLS with uPB-Exo treatment ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1 × 10 6 #/ml HL60 cells or neutrophils were washed with PBS three times, blocked with 2% BSA, and stained, respectively, with PE-labeled anti-CD11a, PE-labeled anti-CD11b, and PE-labeled anti-CD162 antibodies (BD Bioscience, USA) for 30 min at 4°C in the dark as described previously ( 51 ). Then, the cells were washed three times with PBS and analyzed by flow cytometry (BD Accuri C6, BD, USA) with a minimum acquisition of 10,000 events.…”
Section: Methodsmentioning
confidence: 99%
“…VWF unfolding is supposedly initiated under overcritical cumulative shear stress [ 26 ]. The subsequent binding of VWF multimers with platelet GPIb receptors triggers outside-in signalling, i.e., platelet priming [ 47 , 48 ]. Platelet priming leads to platelet activation at which conspicuous functional consequences (e.g., P-selection expression) are observed [ 19 ].…”
Section: Methodsmentioning
confidence: 99%